2018
DOI: 10.1007/s11244-018-1017-z
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Si/Al Ratio for Pd/BEA and Pd/SSZ-13 Used as Passive NOx Adsorbers

Abstract: The mitigation of cold-start emissions involves the development of passive NO x adsorbers (PNA) systems that store NO x at low temperature, being designed to release the trapped NO x at higher temperatures, where downstream NO x reduction catalysts are efficient. Pd-based zeolites (BEA, SSZ-13) with different SAR (Si-to-Al ratio) were used for PNA investigation, and Pd/Ce/Al 2 O 3 catalyst was used as a reference for comparison. In this study, NO x adsorption is investigated at low temperature (80 °C) and it i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
56
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(70 citation statements)
references
References 44 publications
8
56
0
4
Order By: Relevance
“…These results are consistent with the study on propene adsorption by Yoda et al [17]. In that study, they found that propene adsorption occurs on Brønsted acid sites, which are blocked by the presence is known that there are significant interactions between Pd and water, which has been found in passive NOx adsorption studies, where the NO adsorption on Pd/zeolites is significantly reduced in the presence of water [31]. However, DRIFTS studies have shown that NO can replace some of the water species, causing water release [31].…”
Section: Beasupporting
confidence: 91%
See 1 more Smart Citation
“…These results are consistent with the study on propene adsorption by Yoda et al [17]. In that study, they found that propene adsorption occurs on Brønsted acid sites, which are blocked by the presence is known that there are significant interactions between Pd and water, which has been found in passive NOx adsorption studies, where the NO adsorption on Pd/zeolites is significantly reduced in the presence of water [31]. However, DRIFTS studies have shown that NO can replace some of the water species, causing water release [31].…”
Section: Beasupporting
confidence: 91%
“…The results from the TPO experiments are shown in Figure 1. The results in the figure shows that Pd/BEA has a distinct temperature of oxidation centered at 330 • C, which has been confirmed by other studies of BEA impregnated with Pd [31]. The major peak of oxidation for Fe/BEA was found at 230 • C; however, this peak is considerably lower magnitude than the peak associated with the Pd-containing samples.…”
Section: Catalyst Characterisationsupporting
confidence: 84%
“…Its additional charge transfer character is also evident based on the intense pink-purple color of the complex upon CO adsorption ( Fig S5). Previous studies claimed the formation of Pd(IV) cation on various solid supports and zeolites based on (1) the indirect evidence from stoichiometry from XRD refinement 27 (2) DFT-modeling 46 and (3) the presence of the high binding energy feature (relative to PdO with BE of Pd 3d5/2 at 336.5-337.0 eV) in the Pd 3d XPS spectra 24,28,29,47,48 . Interestingly, in some works a feature at 337.7-338.0 eV on ceria supports, for example, 49,50,51 [8][9][10] We also note that upon dehydration either in He or O2, the color of the sample changes from light yellow to light pink (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…However, based on the provided evidence, this Pd/SSZ-13 system selectively forms non-classical Pd +2 (CO)2 fragments and not Pd +3 (CO)2 as previously proposed in the literature. 11,12,24,28 The non-classical nature of this complex is further indirectly corroborated by the fact that its infrared signature does not depend on zeolite type to any significant extent and presents a Pd +2 (CO)2 fragment stabilized as ion pairs (with the Al-associated negative oxygen atoms of zeolite acting as a negative part of the ion pair, whereas Pd +2 and Pd +2 (CO)2 are the positive +2-charged part of the ion pair) in a small (~0.85 nm) SSZ-13 cage ( Fig. S10).…”
Section: Resultsmentioning
confidence: 99%
“…Its additional charge transfer character is also evident based on the intense pink-purple color of the complex upon CO adsorption ( Fig S5). Previous studies claimed the formation of Pd(IV) cation on various solid supports and zeolites based on (1) the indirect evidence from stoichiometry from XRD refinement 27 (2) DFT-modeling 46 and (3) the presence of the high binding energy feature (relative to PdO with BE of Pd 3d5/2 at 336.5-337.0 eV) in the Pd 3d XPS spectra 24,28,29,47,48 . Interestingly, in some works a feature at 337.7-338.0 eV on ceria supports, for example, 49,50,51 was attributed to Pd(IV) ions or PdO2 .…”
Section: Resultsmentioning
confidence: 99%